Preservation of function in the treatment of laryngeal tumors: results of supraglottic laryngectomy - Cavilhas, Pedro (2012)
Objective: The horizontal supraglottic laryngectomy (HSL) is an oncologic surgical technique that allows preservation of laryngeal functions of speech and swallowing with airway protection, but with adequate capacity for tumor excision. The objective of this study is to review a series of patients submitted to HSL.Methods: Retrospective study of HSL carried out in the Department of Otolaryngology of the IPOLFG between 2000 and 2010.Results: There were 32 HSL of which 15 (46.9%) were extended (to the base of the tongue, or pharynx and/or 1 arytenoid), the other 17 (53.1%) were not extended. We observed 2 local recurrences, 3 second primary tumors and 4 patients with distant metastases. Ten patients (31.3%) remained with NGT or PEG for feeding at the end of the study. It was found statistic correlation: (1) between cT and pT staging divergence and the need for extensive surgery, (2) between extended surgery and persistence of NGT (or PEG) for more than 90 days and (3) between the cT and pT staging divergence and classification in the group that includes pT4a and pT3. The estimated survival rate was 89.7% at 12 months and 67.6% at 60 months.Conclusions: This study shows that the HSL is an appropriate surgical technique for the treatment of supraglottic tumors, with survival rates similar to other series and with preservation of laryngeal function in a considerable percentage of patients.